Study of Phenomenology: The Experience of Meeting Nutritional Needs of Infants With Low Birth Weight (LBW) in Positive Deviance Families - Daevi Khairunisa; Yanti Yanti; Ismarwati Ismarwati (poltekkes kemenkes mataram, 2021)
Babies born with Low Birth Weight (LBW) are more prone to experiencing malnutrition problems. Efforts to prevent malnutrition in infants and toddlers can be done through the Positive Deviance approach. Positive Deviance is an individual or group (family) based approach by identifying positive behaviors that allow them to find better solutions to their problems. The purpose of this study was to determine the experience of fulfilling the nutritional needs of infants with a history of LBW in Positive Deviance families. The research design employed in this study was qualitative with a phenomenological approach. The main informants were Positive Deviance mothers, and the supporting informants consisted of Positive Deviance families, non-Positive Deviance mothers, and village midwives. The sampling technique used was purposive sampling. Data collection was carried out through in-depth interviews and documentation studies. The results of this study reveal the experiences of families in fulfilling the nutritional needs of infants with a history of LBW including positive maternal behaviors. For example, Early Initiation of Breastfeeding (IMD), breastfeeding after childbirth, application of breastfeeding correct way to LBW babies, exclusive breastfeeding, complementary breastfeeding, and other efforts if the baby does not have an appetite. Thus, this study implies that positive habits of mothers and families can meet the nutritional needs of infants, especially in increasing the weight of LBW babies to achieve ideal body weight. Therefore, it is necessary to make efforts to make mothers and their Positive Deviance family role models in order to transmit positive habits to other families with babies in preventing malnutrition in infants with LBW history.